The boys of Riverside : a deaf football team and a quest for glory - Fuller, Thomas (Journalist) (Doubleday, 2024)
"The incredible story of an all-deaf high school football team's triumphant climb from underdog to undefeated, their inspirational brotherhood, a fascinating portrait of deafness in America, and the indefatigable head coach who spearheaded the team"--